Evolution of the biochemistry of the photorespiratory C2 cycle. (30th November 2012) - Hagemann, M.; Fernie, A. R.; Espie, G. S.; Kern, R.; Eisenhut, M.; Reumann, S.; Bauwe, H.; Weber, A. P. M.; Rennenberg, H.
Abstract Oxygenic photosynthesis would not be possible without photorespiration in the present day O2‐rich atmosphere. It is now generally accepted that cyanobacteria‐like prokaryotes first evolved oxygenic photosynthesis, which was later conveyed via endosymbiosis into a eukaryotic host, which then gave rise to the different groups of algae and streptophytes. For photosynthetic CO2 fixation, all these organisms use RubisCO, which catalyses both the carboxylation and the oxygenation of ribulose 1, 5‐bisphosphate. One of the reaction products of the oxygenase reaction, 2‐phosphoglycolate (2PG), represents the starting point of the photorespiratory C2 cycle, which is considered largely responsible for recapturing organic carbon via conversion to the Calvin–Benson cycle (CBC) intermediate 3‐phosphoglycerate, thereby detoxifying critical intermediates. Here we discuss possible scenarios for the evolution of this process toward the well‐defined 2PG metabolism in extant plants. While the origin of the C2 cycle core enzymes can be clearly dated back towards the different endosymbiotic events, the evolutionary scenario that allowed the compartmentalised high flux photorespiratory cycle is uncertain, but probably occurred early during the algal radiation. The change in atmospheric CO2/O2 ratios promoting the acquisition of different modes for inorganic carbon concentration mechanisms, as well as the evolutionary specialisation of peroxisomes, clearly had a dramatic impact on further aspects of land plant photorespiration.